Recaudación de Impuestos Prediales del Gobierno Autónomo Descentralizado de Puebloviejo - Montiel Garboa, Maholy Annabel (2019)
The Decentralized Autonomous Government of Puebloviejo is a public entity responsible for ensuring the development of its sectional government to provide a better quality of life to its inhabitants, and has as one of its responsibilities the collection of municipal taxes for its self-management. This entity has a large amount of municipal taxes without being collected taking as object of studies property taxes; There are many circumstances that do not make the collection of taxes something efficient and effective, the problems occur both internally by the Decentralized Autonomous Government because they do not perform well the work related to the collection of these taxes and also externally by the citizens because They show no interest in approaching to cancel